Bøgerne om alt – fortalt af mange: Lene Andersens globale eksistentialisme - Hansen, Kim Toft (Academic Quarter | Akademisk kvarter, 2011)
In Books about the lot - told by a lot. Lene Andersen's global existentialism, Kim Toft Hansen presents and analyzes Baade og, a comprehensive and distinctive work in five volumes by Lene Andersen. You can place this intellectual performance as a kind of map in which different genres and sciences are mixed. An especially interesting theme in this issue of Academic Quarter is Lene Andersen's ideas of a global existentialism containing a critique of religion, science and business: scientific arrogance, religious stupidity and commercial cynicism. Simultaneously there is an appeal to those cultural and economic systems to work as centripetal forces and to contribute to the common good acting positively e.g. promoting prosperity, education, formation, community and awareness about responsibilities.